Google’s Influence on Global Business Models in Journalism: An Analysis of Its Innovation Challenge - Alfred Hermida; Mary Lynn Young (Media and Communication, 2024)
This study investigates how Google is shaping journalism innovation, particularly in business models, through an analysis of one of its global funding competitions, the Innovation Challenge. It adds to an understanding of the impact of platforms on journalism through a descriptive analysis of 354 projects funded between 2018 and 2022 in 78 countries and five regions. Grant recipients were largely for-profit journalism organizations, with a significant US focus. Projects related to audience engagement, business models and distribution dominated the published winning innovation proposals, accounting for 72.6% of funded projects. The three areas were closely connected as they were mostly related to plans to increase reader revenue. Findings suggest that the Innovation Challenge validates reader revenue as the key innovation in business models through a funding competition aligned with Google’s global industry and government relations interests. The orientation is problematic as it narrows journalism innovation to a financial issue, with audiences as the answer, even though people are largely unwilling to pay for news and journalism is considered a public good rather than simply a commercial product.